Oilseed farming in Myanmar: An analysis of practice, productivity, and profitability: Assessment of the 2023 monsoon - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
We have analyzed oilseed production patterns, productivity, and profitability for the 2023 monsoon season from the Myanmar Agriculture Performance Survey (MAPS), conducted at the beginning of 2024. This survey encompassed plots managed by 802 oilseed producers, distributed across all states/regions of the country. Our findings reveal: 1. Overall, oilseed productivity increased by an average of 2 percent during the 2023 monsoon compared to the previous year. Performance differed by crop with soybean and sesame experiencing moderate increases in yield, while groundnut and sunflower witnessed a decline in average yields of one percent. This mediocre performance stemmed from low input usage (particularly fertilizer), similar labor inputs, and a high occurrence of natural shocks, notably pests, diseases, and weeds, and heavy rain and storms. 2. Despite decreasing fertilizer prices, chemical fertilizer use remained low in oilseed production, with 45 percent of farmers using chemical fertilizer in monsoon 2023. Further, chemical fertilizer use did not increase in oilseed production compared to the previous monsoon. 3. Organic fertilizer use, on the other hand, is high in oilseed production, as 63 percent of farmers applied it in the 2023 monsoon season. During this time, organic fertilizer was used by 74 percent of groundnut farmers and 76 percent of oilseed farmers in the Dry Zone. This is due to the availability of organic manure in the Dry Zone where oilseed production is high. 4. Groundnut, soybean, and sesame farmers relied on seeds saved from last year’s harvest, while 67 percent of sunflower farmers purchased seeds from ag-input retailers or the government. The percentage of oilseed farmers using self-preserved seed – instead of obtaining it from the market - increased by 9 percentage points compared to last monsoon. 5. Draught animal ownership remains important for oilseed production, especially in the Dry Zone. Seventy-one percent of oilseed farmers used draught animals in production, with 50 percent using their owned draught animals. 6. Thirty-nine percent of oilseed farmers reported being impacted by climatic or other production shocks during this monsoon, with pests, diseases, and weeds (reported by 36 percent of farmers who experienced shocks), heavy rain/ storms (reported by 34 percent), droughts (reported by 22 percent), and irregular rainfall (reported by 21 percent) having significant adverse effects on yields. 7. Oilseed prices at the farm level increased by between 20 (soybean) and 45 (sunflower) percent, reflecting changes in international oilseed prices as well as the depreciation of the MMK. 8. Real – in terms of the cost of an average food basket – gross margins from oilseed farming during the monsoon of 2023 increased by between 2 (soybean and groundnut) and 12 (sesame) percent compared to the previous year. Real sunflower gross margins declined. At the same time, nominal profits increased by 33 percent since the previous monsoon. High price inflation tempered the increase in real profits. 9. Twenty percent of oilseed farmers faced significant issues in terms of marketing, including low prices for crops, insecurity, and having trouble reaching traders. These issues likely decreased the profitability of oilseed farming for the affected farmers. 10. Oilseed farmers reflecting on this monsoon compared to last, perceived higher profits, suggesting that the oilseed sector continues to be a lucrative choice for farmers. These findings have several policy implications: 1. Ensure access to quality seeds: Reusing seeds from previous seasons reduces yields, especially when combined with climate shocks. The private sector should make quality seeds and seeds with high oil content available to boost oilseed crop yields. 2. Promote organic fertilizer use: Organic fertilizer is predominantly used in the Dry Zone. Expand its use to other agro-ecological zones to improve long-term soil fertility and help farmers mitigate the impact of fluctuating chemical fertilizer prices. The private sector and NGOs through in-person and online platforms can provide training on making compost from farm residues for farmers without access to animal manures. 3. Enhance pest and disease management: The private sector should provide farmers with access to better pest and disease management resources, including training and access to effective, environmentally friendly pesticides and herbicides. 4. Strengthen climate resilience: The private sector can strengthen climate resilience by developing and disseminating climate-resilient agricultural practices, providing training on drought-tolerant and flood-resistant crop varieties through in-person and online platforms, and offering financial incentives and technological support to farmers. 5. Create secure marketing channels: Farmers face low crop prices and safety issues during trade, along with difficulties in reaching traders due to security concerns. Develop secure and stable marketing channels to address these challenges. 6. Increase loans for oilseed crops: Given the higher production costs of groundnut, sesame, and soybean compared to sunflower, MADB should increase their loan amounts for these crops to enhance their productivity. The private sector could also lend money to oilseed farmers, given the increase in oilseed production stemming from their perceived profitability and importance to the government.